(untitled) (Research, Society and Development, 2022)
Fungi are a promising alternative source of oil to produce biodiesel, still very little known. The identification of a species with desirable characteristics is a fundamental component to achieve the economic viability of the process. The study aimed to carry out the evaluation of the fungus Aspergillus terreus in different culture media and different temperatures, the production of fungal biomass and in line with obtaining the profile of methyl esters of fatty acids. The fungal biomass revealed that in the NBRIP medium at both a temperature of 29 ºC and 36 ºC, it resulted in a great potential in the production of saturated fatty acids (SFA), which have excellent combustion properties, reaching values of 35.89 and 34,89%, respectively. For most species, the fuel would need to be mixed to make up culture conditions to be optimized and achieve the correct lipid profile, so that the fungal fuel meets European biodiesel production standards (EN 14214). Aspergillus terreus from iron ore tailings proved to be a promising microbial biomass as an energy source in the production of biodiesel.